Quantification of training in competitive sports. Methods and applications. - Hopkins, W. G. (Sports Medicine, 1991)
The training of competitive athletes can be assessed by retrospective questionnaires, diaries, physiological monitoring and direct observation of training behaviour. Questionnaires represent the most economical, most comprehensive and least accurate method. Diaries are more valid, but their drawbacks for long term quantitative studies are poor compliance and difficulties in processing the data they generate. Physiological monitoring (of oxygen consumption, heart rate or blood lactate concentration) provides objective measures of training intensity, and direct observation gives valid measures of most aspects of training; however, these methods are impractical for continuous, long term use.